Laruelle and Non-Photography - Fardy, Jonathan. author. aut Link
XI, 73 p.
Keywords: This book provides a critical introduction to François Laruelle’s writings on photography, with a particular focus on his two most important books on photography: The Concept of Non-Photography and Photo-Fiction, a Non-Standard Aesthetics. By unpacking and contextualising these works, this study provides a useful starting point for students and scholars who want to better understand Laruelle’s larger project, which he calls “non-philosophy”, or more recently, “non-standard philosophy”. With clear and concise explanations of the basics of non-philosophy, Laruelle and Non-Photography demonstrates how Laruelle's thought challenges standard, philosophical approaches to photography, and culminates in a novel theory of "non-photography.".